Are there differences between the loading of an anaerobic capacity test and an agility test in basketball players? - Mancha-Triguero, D.; Gómez-Carmona, C. D.; Gamonales, J. M.; Garcia-Rubio, J.; Ibanez, S. J. (Revista Brasileira de Cineantropometria e Desempenho Humano, 2020)
The objective of this article was to know players` needs in the selected tests, to search for differences between categories and to know if there is any relationship between different tests. The sample consists of 2 teams (u-14, u-16, n=24), which were equipped with a WimuR inertial device. The selected tests were 2 agility tests and a lactic anaerobic capacity test. Neuromuscular and kinematic variables were selected. Descriptive analysis, inferential analysis and analysis of correlation among variables were carried out. Once players` needs are described, there are no significant differences among kinematic variables depending on the sample category. Nonetheless, there is relationship between kinematic and neuromuscular variables of the different tests. It is frequently claimed that capacity tests are those that cause more fatigue in athletes. For this reason, an analysis was carried out comparing a lactic anaerobic capacity test with an agility test in its two versions. The obtained results can facilitate the work and the evaluation time of a physical condition test since results of athletes in a capacity test could be known by performing tests of lesser requirement. In addition, this would avoid players from experiencing a situation of maximum effort and possible injury, also saving training time.